On Ministering to ‘Certayne Devoute and Religiouse Women’: Bishop Fox and the Benedictine Nuns of Winchester Diocese on the Eve of the Dissolution - Greatrex, Joan (Studies in church history, 1990)
It was not until after almost thirty years in the royal service and on the episcopal bench that Richard Fox retired to Winchester and turned his full attention to his pastoral office. There, at the age of sixty-eight and afflicted with failing eyesight, he set out to reform his flock. In a letter to Cardinal Wolsey he admitted that his mind had been ‘trowled nyght and daye with other mens enormites and vices’, and that he was anxious to ‘do soom satisfaccion for xxviij years negligence’. Ten years later there was a modest undertone of relief in his report to the Cardinal: